2023
DOI: 10.2147/rmhp.s422705
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with High Rates of Caesarean Deliveries: A Cross Sectional Study Classifying Deliveries According to Robson in Mengo Hospital Kampala

Susan Nantume,
Eric Murungi Baluku,
Doris Kwesiga
et al.

Abstract: Introduction The number of caesarean section (CS) continues to rise worldwide. CS can improve outcomes in infants and mothers. However, if used improperly, the potential harm can outweigh the potential benefits. Aim The study was to determine the factors associated with high cesarean section rates at Mengo Hospital. Methods This cross-sectional study used a mixed-method approach that included a retrospective review of 1276 casebooks using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Moreover, another study from a private tertiary hospital in Nigeria reported that Robson Group 5 had the largest contribution to the total cesarean section rates, emphasizing the impact of previous cesarean deliveries on the decision for subsequent cesarean sections [24]. The cesarean section rates across Groups 3 and 4 illustrate how labor management and obstetric history influence delivery decisions, with spontaneous labor in multiparous women leading to significantly lower cesarean rates compared to those with induced labor or previous cesareans [25]. High cesarean rates in Groups 6 and 7 for breech presentations and in Groups 8, 9, and 10 for multiple pregnancies, abnormal lies, and preterm deliveries underscore a preference for cesarean delivery in managing complex or high-risk obstetric scenarios [26].…”
Section: Robson Classification Analysis and Its Implications For Cesa...mentioning
confidence: 99%
“…Moreover, another study from a private tertiary hospital in Nigeria reported that Robson Group 5 had the largest contribution to the total cesarean section rates, emphasizing the impact of previous cesarean deliveries on the decision for subsequent cesarean sections [24]. The cesarean section rates across Groups 3 and 4 illustrate how labor management and obstetric history influence delivery decisions, with spontaneous labor in multiparous women leading to significantly lower cesarean rates compared to those with induced labor or previous cesareans [25]. High cesarean rates in Groups 6 and 7 for breech presentations and in Groups 8, 9, and 10 for multiple pregnancies, abnormal lies, and preterm deliveries underscore a preference for cesarean delivery in managing complex or high-risk obstetric scenarios [26].…”
Section: Robson Classification Analysis and Its Implications For Cesa...mentioning
confidence: 99%